(untitled) (Medical Forum Monthly, 2024)
Background: Anthropology is the most intimate humanistic explanation of human diversity as regards various small and large scales societies of the world. Anthropology aims to provide modern human civilization with understandable accounts of how human diversity that are not rooted in racial discrimination rather to bring us an opportunity to seek underlying rationalities and intellects associated with various historical, environmental, ecological, geographical, demographical, social, political and cultural compartmentalization and assortments. Objective: To help health personnel to understand the local mind about the health and eudaemonia as perceived and practiced by the rural population. Study Design: Observational (exploratory) study. Place and Duration of Study: This study was conducted in the Union Council of Sacha Soda in the Tehsil and district of Sheikhupura district of the Punjab province from January 2011 to December 2011. Materials and Methods: This study was based upon an intensive field works for three years in a Punjabi village Sacha Soda of Sheikhupura district on indigenous health paradigms. It is an anthropological reflection of an indigenous healthy dichotomy to which the researchers have termed “Sehat-Tandarusti” existing and prevailing in the rural Punjab. Results: Punctuality in taking dinner (95.3%), washing hands before taking food (92.9%), mild walk after food (82.1%) and chewing sugar cane and maze as exercise of teeth (77.9%) were the most common good eating habits. Majority of the villagers were going into beds earlier (95%) and a high percent were getting up early (75%). Their first preference in case of illness was seeking help from Faith healers (86.1%) and the herbalists (88.9%). Conclusion: There is a need to adopt the indigenous health perspective on Sehat (Eudaemonia) in order to promote the social awareness and effectively mobilize the populations towards better hygienic education and raising social responsibility among populations to contribute in making their livelihoods health friendly. The reinstating of the traditional health seeking system of practices can help the local populations to seek medical advices at local level as well as removing a threat from already overburdened urban health facilities